Increasing Road Traffic Injuries in Underage Motorcyclists - Piyapromdee, MD, Urawit; Adulyanukosol, MD, Varinthorn; Lewsirirat, MD, Supphamard (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Traffic accident is the second most common pediatric injury in Thailand. Children aged less than 15 years old are not allowed to get a motorcycle driving license. But the number of underage motorcyclists is still high. The purpose of this study is to evaluate the number of traffic injuries in underage motorcyclists and the trend of this problem. Methods: A retrospective review of traffic accident cases at Maharat Nakhon Ratchasima Hospital from October 2009 to September 2013 was performed. Motorcyclists aged less than 15 years old were included in the study. The number of patients per year, risk behaviors, the diagnosis, complications and incidence rate were collected from the traffic injury surveillance database. Results: In total, 44,335 patients were referred to Maharat Nakhon Ratchasima Hospital. There were 5,320 injured children, 1,373 (25.81%) patients were underage motorcyclists. There were 291, 318, 391 and 373 underage motorcyclists each year, respectively. Only 225 (16.54%) were wearing a helmet, 55 cases (4.04%) had consumed alcohol before the accident. The number of severe cases, such as head injuries, abdominal injuries, or fractures increased year on year, especially the fractures; the incident rate ratio of the fracture case was 10.23% per year (P=0.005). Death cases per year were 2, 4, 7 and 6, respectively. The most common cause of death was head injury. Conclusion: Traffic accidents involving an underage motorcyclist are high and increasing every year. If we can strictly control underage motorcyclists not to ride motorcycles, the accidents may decrease.